LoRaWAN Network Performance Test - Drotar, Istvan; Lukacs, Balazs; Kuczmann, Miklós (Acta Technica Jaurinensis, 2020)
There are several types of wireless IoT (Internet of Things) networks based on the connection distance between two communicating devices. For covering wide areas, LPWAN (Low Power Wide Area) networks can provide a good solution. These networks provide big coverage and low power consumption. One of the most popular LPWAN network is LoRaWAN (Long Range Wide Area Network). LoRaWAN networks are ideal for sending infrequent, small messages through long distances. In this article the network’s capacity, coverage and energy consumption have been tested. These are the most important attributes when designing a LoRaWAN network, so it can satisfy the requirements of LPWAN networks.